Effects of integrating Feldenkrais method with dynamic neuromuscular stabilization exercises on clinical outcomes in older women with nonspecific chronic low back pain: A randomized controlled trial - Farzaneh Saki; Marziyeh Ziya (BMC Geriatrics)
Abstract Background The Feldenkrais Method and Dynamic Neuromuscular Stabilization (DNS) exercises have each demonstrated benefits for managing chronic low back pain (CLBP). However, limited research has explored their combined efficacy, particularly in older women with nonspecific CLBP. This study aimed to assess the clinical effects of combining these interventions. Methods This randomized controlled trial (RCT) was conducted over eight weeks (July 17 to September 11, 2024) at the Sports Sciences Laboratory of Bu-Ali Sina University, Hamedan, Iran. Thirty elderly women, aged 60–80 years, with nonspecific CLBP were randomly assigned using a computer-generated sequence to either a DNS group (n=15) or a combined DNS exercises and Feldenkrais Method (DNSFME) group (n=15). The DNS protocol consist of stabilization exercises targeting core control, while the Feldenkrais Method involved awareness and movement re-education sessions. Outcome measures were pain intensity, measured by the Visual Analog Scale (VAS), lumbar flexion and extension range of motion (ROM), assessed via Schober’s test, and kinesiophobia evaluated using the Tampa Scale for Kinesiophobia (TSK). Assessments were conducted at baseline and post-intervention. Between-group differences were analyzed using analysis of covariance (ANCOVA) adjusted for baseline values, and paired t-tests were used to assess within-group changes (P≤0.05). Results Participants were older women (mean age 65.44 ± 3.99 years) with no significant baseline differences in demographic or clinical characteristics between groups. The DNSFME group showed significantly greater improvements compared to the DNS group in pain intensity (p = 0.010, partial η² = 0.255), kinesiophobia (p < 0.001, partial η² = 0.493), lumbar flexion ROM (p = 0.007, partial η² = 0.273), and lumbar extension ROM (p < 0.001, partial η² = 0.429). Within-group improvements were significant for both groups. For the DNS group: pain (p < 0.001, 95% CI: 3.15 to 4.57), kinesiophobia (p < 0.001, 95% CI: 10.25 to17.18), lumbar flexion ROM (p < 0.001, 95% CI: –1.57 to –1.09), and lumbar extension ROM (p < 0.001, 95% CI: –0.81 to–0.50). For the DNSFME group: pain (p < 0.001, 95% CI: 4.27 to 5.72), kinesiophobia (p < 0.001, 95% CI: 17.57 to 24.16), lumbar flexion ROM (p < 0.001, 95% CI: -2.16 to -1.59), and lumbar extension ROM (p < 0.001, 95% CI:-1.12 to -0.84). Conclusion Both interventions effectively alleviated pain and fear of movement while enhancing lumbar range of motion in older women with chronic low back pain. The combined intervention, integrating the Feldenkrais Method with Dynamic Neuromuscular Stabilization exercises, yielded superior clinical outcomes, supporting its incorporation into rehabilitation programs to improve functional independence and quality of life